Community Involvement and ITS Impact On School Success In Madagascar - Ralaivao Hanginiaina Emynorane; Marolahy Jacquot Urbain; Rabibisoa Giovanni; Hangivola Emyblonde Ratna; Soameva Léa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to examine how community involvement influences school success in Sakaraha, a semi-urban district in the Atsimo-Andrefana region of Madagascar, where educational progress is often hindered by limited resources and social inequality. It sought to understand how local actors participate in school activities, the barriers they encounter, and the effects of their engagement on educational outcomes. A qualitative approach was employed, using semi-structured interviews, focus group discussions, and document analysis to collect data from 25 participants, including school principals, teachers, parents, community leaders, and education officers selected through purposive sampling. Thematic analysis was applied to identify key patterns and perspectives regarding community participation and its impact on school performance. The findings indicate that communities in Sakaraha contribute actively through practical actions such as maintaining school facilities, organizing local initiatives, and supporting student discipline; however, their participation remains limited in decision-making and long-term educational planning. Socioeconomic constraints, particularly poverty, low literacy levels, and weak communication between schools and families, continue to limit sustained collaboration. Despite these challenges, community participation was found to enhance student motivation, attendance, and the overall school environment, demonstrating its significance as a key driver of educational improvement. Strengthening participatory mechanisms and equipping communities with leadership and communication skills could transform this involvement into a more strategic and sustainable force for school development. The study highlights the need for stronger collaboration among the Ministry of National Education, local authorities, and non-governmental organizations (NGOs) to promote inclusive governance and shared responsibility in education. Enhancing community-school partnerships in Sakaraha and similar regions may contribute to a more equitable, resilient, and effective education system that supports long-term student success and community development.